Fully differential cross sections in single ionization of helium by ion impact: Assessing the role of correlated wave functions - Ciappina, Marcelo Fabián (2008)
We study the effect of final state dynamic correlation in single ionization of atoms by ion impact analyzing fully differential cross sections (FDCS). We use a distorted wave model where the final state is represented by a Φ 2 type correlated function, solution of a non-separable three body continuum Hamiltonian. This final state wave function partially includes the correlation of electron-projectile and electron-recoil relative motion as coupling terms of the wave equation. A comparison of fully differential results using this model with other theories and experimental data reveals that inclusion of dynamic correlation effects have little influence on FDCS, and do not contribute to a better description of available data in the case of electronic emission out-of scattering plane.